Perceived overqualification repatriates: post hoc analysis for traditional and alternative forms / Maggie Mei Kei Chong, Raida Abu Bakar and Sharmila Jayasingam - Mei, Maggie Kei Chong; Abu Bakar, Raida; Jayasingam, Sharmila (Faculty of Business and Management, 2022)
Repatriates perceived the discrepancy in utilizing their enhanced international experiences upon returning home, resulting in them being perceived as being overqualified, and led to low retention rates. Besides long-term international assignments, the literature on repatriation of alternative forms of international assignment have increased in popularity. Using the snowball sampling technique, a total of 147 returned questionnaires from Malaysian repatriates were valid after data screening. The SmartPLS 3.0 software was applied to conduct structural model analysis and multi-group analysis. It appears that repatriates who perceived that they were overqualified, often exhibited a low affective commitment and high continuance commitment. Beyond that, the impact of the perceived overqualification was prominent among traditional repatriates, as opposed to the alternative form of repatriates, based on the post-hoc findings. This study drew on the relative deprivation theory, and highlighted that a proxy for successful repatriation was to reduce the repatriate’s deprivation, in order to maintain affective and continuance commitment of repatriates. Therefore, this study acknowledges the emerging notion and believe that the post-hoc findings should put the organization on alert, to help maintain the organizational commitment of their valuable repatriates upon returning from both types of international assignments.